Análise de custos de produção e indicadores econômicos da bovinocultura leiteira : estudo de caso em uma propriedade rural no município de Firminópolis –GO - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
Production costs and economic indicators are necessary elements to measure the success or failure of dairy cattle. The objective was to analyze the production costs and economic indexes of dairy cattle in a rural property in the municipality of Firminópolis -GO, with a time frame from 2011 to 2018. For the interpretation of the data, the methodology of the production cost structure was used: cost effective operating cost, total operating cost and total cost. Gross margin, net margin, break-even point, profitability and profitability, indicators of economic efficiency of the property were analyzed. Of the components of the effective operating cost, food and concentrates, permanent labor and medicines and vaccines, presented greater representativeness. Average revenues from exclusively selling milk were not sufficient to cover total costs in the first three years of the analysis. When animal sales were added, the revenue allowed gross margin and positive net margin, which enabled the property to survive in theshort and long term, however, the breakeven point and profitability were reached in the medium term. Average profitability was positive at 7.5%, which generated the capitalization of the producer to replace production goods, not condemning them to scrap.
Keywords: Gestão rural; Planejamento; Rentabilidade; Sistemaprodutivo; Rural management; Planning; Profitability.; Productive system; CIENCIAS AGRARIAS